Different "metabolomic niches" of the highly diverse tree species of the French Guiana rainforests - Gargallo-Garriga, Albert; Sardans, Jordi; Granda, Victor; Llusià, Joan; Peguero, Guille; Asensio, Dolores; Ogaya, Romà; Urbina, Ifigenia; Van Langenhove, Leandro; Verryckt, Lore T; Chave, Jérome; Courtois, Elodie A; et al. (Scientific reports, 2020)
Tropical rainforests harbor a particularly high plant diversity. We hypothesize that potential causes underlying this high diversity should be linked to distinct overall functionality (defense and growth allocation, anti-stress mechanisms, reproduction) among the different sympatric taxa. In this study we tested the hypothesis of the existence of a metabolomic niche related to a species-specific differential use and allocation of metabolites. We tested this hypothesis by comparing leaf metabolomic profiles of 54 species in two rainforests of French Guiana. Species identity explained most of the variation in the metabolome, with a species-specific metabolomic profile across dry and wet seasons. In addition to this "homeostatic" species-specific metabolomic profile significantly linked to phylogenetic distances, also part of the variance (flexibility) of the metabolomic profile was explained by season within a single species. Our results support the hypothesis of the high diversity in tropical forest being related to a species-specific metabolomic niche and highlight ecometabolomics as a tool to identify this species functional diversity related and consistent with the ecological niche theory.
Keywords: Analysis of Variance; Seasons; Francouzská Guyana; listy rostlin; druhová specificita; shluková analýza; Species Specificity; Plant Leaves; Metabolomics; roční období; Least-Squares Analysis; deštný prales; metoda nejmenších čtverců; stromy; metabolomika; diskriminační analýza; analýza rozptylu; metabolom; Discriminant Analysis; French Guiana; Metabolome; Cluster Analysis; Trees; Rainforest